Encyclopedic spirit and technical mentality: Contributions for a reflection on the industrialization processes in the province of Catamarca - Argentina in the second half of the 19th century (Culturas Científicas, 2023)
This work aims to provide some elements for a reflection on the industrialization processes in the province of Catamarca - Argentina in the second half of the nineteenth century. To orient ourselves in this direction, we will start from the project of a genetic encyclopedia proposed by the philosopher Gilbert Simondon as a proposed approach. Then we will analyze the encyclopedic spirit present in the economic writings of Federico Schickendantz and Samuel Lafone Quevedo structured as teaching machines. Finally, we will present the description of two technical objects created by D. Mardoqueo Molina y Bazán elaborated in these writings. We consider that these technical objects provided a paradigm of intelligibility for the construction of certain images of the future of industrial activity in the province of Catamarca in these writings. From our perspective, the lack of a metastable state at the social level, necessary to amplify these images of the future, prevented the development of a technical mentality.
Keywords: Keywords: History, Philosophy, Industry, Paradigms, Optimization; History; Philosophy; Industry; Paradigms; Optimization